Electrospinning and 3D printed hybrid bi-layer scaffold for guided bone regeneration. (15th November 2021) - Liu, Jie; Zou, Qin; Wang, Chenxin; Lin, Mingyue; Li, Yufan; Zhang, Rui; Li, Yubao
Graphical abstract: Highlights: A bi-layer scaffold consists of electrospinning membrane and 3D printing scaffold. The upper layer membrane could promote L929 fibroblast adhesion and proliferation. The lower layer porous scaffold could promote osteogenic differentiation of BMSCs. In vivo studies confirm the beneficial features of the bi-layer scaffold for GBR. Abstract: The guided bone regeneration (GBR) concept has been extensively utilized to treat periodontal defects in clinical practice. However, the repair efficacy of the currently available GBR membranes is often compromised by their limited alveolar bone regeneration potential, insufficient mechanical strength and inadequate space maintenance duration. In this paper, a novel hybrid bi-layer scaffold was fabricated using electrospun polycaprolactone/gelatine (PCL/Gel) nanofibre membranes combined with 3D printed PCL/Gel/nano-hydroxyapatite (n-HA) scaffolds. Their manipulation parameters and microstructures were investigated, and biological studies of in vitro and in vivo bone regeneration were carried out. The heparin-conjugated PCL/Gel fibrous membrane could significantly promote L929 fibroblast adhesion and proliferation. The PCL/Gel/n-HA (PGH) scaffold could promote attachment, growth and osteogenic differentiation of BMSCs. After 20 weeks, the defect sites in the hybrid bi-layer scaffold group showed a higher degree of new bone formation than that in the control group, indicating that this is a promising material combination for GBR.